Implementation of Sharia Economic Values in BULOG’s Intervention Policy on Rice Grain Prices in Duampanua - Gustia Gustia; Syahriyah Semaun; Islamul Haq; Muliati Muliati; Damirah Damirah (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2026)
This study aims to analyze the implementation of Islamic economic values in the intervention policy of Perum Bulog on rice grain prices in Duampanua District, Pinrang Regency. Price fluctuations and the dominance of middlemen as the main buyers often force farmers to sell their harvest below the Government Purchasing Price (HPP). This condition indicates that Bulog’s role as a price-stabilizing institution has not been fully optimal in maintaining price stability and protecting farmers’ welfare. This research employs a descriptive qualitative method with a case study approach and field research design. Data were obtained through in-depth interviews with farmers, middlemen, and Bulog officials, supported by secondary data from policy documents and relevant literature. The results show that Bulog’s interventions through HPP policies, grain procurement, and market operations have contributed to price stabilization; however, implementation remains uneven due to limited access, bureaucratic obstacles, and lack of socialization. From the perspective of Islamic economics, the values of Siddiq (honesty) and Amanah (trustworthiness) are reflected in price determination and farmer protection but have not been fully and consistently applied in practice. The value of Fathonah (wisdom and intelligence) appears in procurement and infrastructure policies but has not effectively reached remote production areas. Meanwhile, Tabligh (transparency and dissemination of information) remains weak, resulting in the incomplete realization of Maṣlaḥah (public welfare) for farmers.